Study of Some Mechanical and Physical Properties of Cold Curing Acrylic Resin Reinforced with Particle Yttrium Oxide (Journal of the College of Basic Education, 2022)
Over the past thirty years, composite materials are being used extensively in many applications; this is due to proven fact that composite materials such as high stiffness, high strength, low thermal conductivity. In this study we used particle Yttrium oxide (5%, 10%, 15% and 20%) as reinforcement to cold curing acrylic resin. Many mechanical and physical tests were used to determine the properties of the prepared composite material which involved tensile strength, toughness, hardness, thermal conductivity, density and water absorption. The results had shown that the tensile strength and toughness decreased with increasing weight fraction of Y2O3. The hardness has been increased with increasing weight fraction of yttrium oxide especially at (5%, 10%, 15%). thermal conductivity increased with increasing volume fraction of yttrium oxide, maximum density was obtained at (15% wt.) of Y2O3 reinforced composites. Water absorption decreased with increasing weight fraction of Y2O3.